THERMODYNAMIC PECULIARITIES OF III-V COMPOUNDS FREE STANDING NANOMETER FILMS CRYSTALLIZATION BY SOLUTION TECHNIQUE - Antoschenko, V.S.; Lavrischev, O.A.; Francev, Yu.V. (Recent Contributions to Physics, 2008)
The phase balance analysis of quaternary systems on the basis of III-V compounds containing Sn or Bi as a main component is carried out. It is shown, that the course of liquidus and solidus isotherms defines possibility of III-V free-standing nanometer films crystallisation.